Privatizing subjectivities: how New Public Management (NPM) is designing a “new” professional in education - Anderson, Gary (Revista Brasileira de Política e Administração da Educação - Periódico científico editado pela ANPAE, 2017)
This study presents a critical analysis of how education and management have been re-articulated by neoliberal policies and practices of new political management. It analyzes these changes in the social sectors and compares them with international policies. These new flexible organizations are part of a growing model of neoliberal business to which some social theorists attribute a growing inauthenticity in organizations (Sennett, 1998), and a development of greater flexibility to respond to the markets and not to satisfy the human needs of those who work in these markets. The study concluded that the competitive model of school management is not only changing what professionals do but who they are. Competition is rebuilding their own identities, both personal and professional.